Exploratory Factor Analysis of SCL90-R Symptoms Relevant to Psychosis - Javad Amini; Vandad Sharifi; Jafar Bakhshaie (Iranian Journal of Psychiatry, 2011)
"nObjective: Inconsistent results have been reported regarding the symptom dimensions relevant to psychosis in symptoms check list revised (SCL90-R), i.e., "psychoticism" and "paranoid ideation". Therefore, some studies have suggested different factor structures for questions of these two dimensions, and proposed two newly defined dimensions of "schizotypal signs" and "schizophrenia nuclear symptoms". We conducted an exploratory factor analysis on the items of these two dimensions in a general population sample in Iran. "nMethod: A total of 2158 subjects residing in Southern Tehran (capital of Iran) were interviewed using the psychoticism and paranoid ideation questions in SCL90-R to assess severity of these symptom dimensions. Factor analysis was done through SAS 9.1.3 PROC FACTOR using Promax rotation (power=3) on the matrix of "polychoric correlations among variables" as the input data. "nResults: Two factors were retained by the proportion criterion. Considering loadings >= 0.5 as minimum criteria for factor loadings, 7 out of 10 questions  from psychoticism ,and 3 out of 6 questions from paranoid ideation were retained, and others were eliminated. The factor labels proposed by the questionnaire suited the extracted factors and were retained. Internal consistency for each of the dimensions was acceptable (Cronbach's alpha 0.7 and 0.74 for paranoid ideation and psychoticism respectively). Composite scores showed a half-normal distribution for both dimensions which is predictable for instruments that detect psychotic symptoms. "nConclusion: Results were in contrast with similar studies, and questioned them by suggesting a different factor structure obtained from a statistically large population. The population in a developing nation (Iran) in this study and the socio-cultural differences in developed settings are the potential sources for discrepancies between this analysis and previous reports.